Pengaruh Penambahan Pupuk Hayati dan POC Urine Domba Terhadap Pertumbuhan dan Hasil Tanaman Padi (Oryza sativa L.) Varietas Inpari 32 - Tedi, Tedi; Azizah, Elia; Samaullah, Yamin (JURNAL AGROPLASMA, 2025)
Rice is an agricultural commodity that produces rice as the staple food of more than 95% of the Indonesian population. The national demand for rice has reached more than 30 million tons per year. On the other hand, the challenges faced in procuring rice production are increasingly severe, among others: The rate of population growth and the relatively high level of rice consumption, some fertile paddy fields have been converted to other businesses, and the level of productivity of paddy fields is declining due to the low content of soil organic matter. According to the Ministry of Agriculture, the program to increase rice production that can be done quickly is intensification with fertilization, both inorganic and organic fertilizers. This research was conducted from August 2023 to November 2023. In Pasirjengkol Village, Majalaya District, Karawang Regency, West Java. The research method used is the experimental method, employing a Single Factor Randomized Block Design (RBD) consisting of 5 treatments, each repeated 5 times. The treatments include P0 (Control), P1 (Biofertilizer), P2 (LOF of Sheep Urine), P3 (Biofertilizer (50%) + LOF of Sheep Urine (50%)), P4 (Biofertilizer (100%) + LOF of Sheep Urine (100%)). The observational data were analyzed using analysis of variance and further tested with the Duncan Multiple Range Test (DMRT) at a 5% significance level. The research results indicate that treatment P4 (Biofertilizer (100%) + LOF of Sheep Urine (100%)) gave the highest results on the growth and yield of INPARI 32 rice plants in all observation parameters. Keywords: INPARI 32 rice, sheep urine POC, biofertilizer